Low energy synthesis of anhydrite cement from waste lime mud. Issue 3 (8th December 2022) - Kamarou, Maksim; Moskovskikh, Dmitry; Chan, Ho Lun; Wang, Haitao; Li, Tielong; Akinwande, Abayomi Adewale; Romanovski, Valentin
Abstract: Background: The re‐use of waste is the most important aspect of sustainable development for human health and environmental protection. Millions of tons of hazardous spent sulfuric acid and lime mud are produced by water treatment facilities every year. Unlike other types of waste, lime mud can sometimes be used for the thermal regeneration of lime. However, this approach requires a high energy consumption and, thus, cannot be considered a sustainable or green process. Compared to the latest research, the method presented here allowed for the production of anhydrite in one step at very low temperatures and in a short time while also bypassing the stage of gypsum phase formation. Results: Calcium sulfate anhydrite was synthesized from the water treatment waste of lime mud by a low‐temperature method at temperatures of 25 and 45 °С. The resulting samples were composed of anhydrite with different crystal morphologies. This was confirmed by XRD, DTA, SEM, TEM, and thermochemical calculations. Dependences of the influence of the shape of crystals on the main technological properties of anhydrite cement and the influence of additives on the activation of the binding properties were established. Conclusion: The research shows that different types of calcium sulfate anhydrite require different additives and in different amounts. Introducing the optimal composition of additives‐activators made it possible to obtain anhydrite cement with a water‐anhydrite ratio of 0.25, an onset of setting no earlier than 40 min, an end of setting no later than 12 h, and a strength of 28.8 MPa. © 2022 The Authors. Journal of Chemical Technology and Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry (SCI).